A Novel Dendrite‐Free Lithium Metal Anode via Oxygen and Boron Codoped Honeycomb Carbon Skeleton. Issue 11 (4th February 2022) - Xie, Yiwen; Zhang, Haiyan; Yu, Jiale; Liu, Zhenjiang; Zhang, Shangshang; Shao, Huaiyu; Cao, Yuliang; Huang, Xifeng; Li, Shengkai
Abstract: Lithium (Li) metal is an excellent anode of Li ion batteries because of its high theoretical capacity and the low redox potential compared to other anodes. However, the uncontrollable growth of Li dendrites still incurs serious safety issues and poor electrochemical performances, leading to its limited practical application. An oxygen and boron codoped honeycomb carbon skeleton (OBHcCs) is reported and a stable Li metal‐based anode is realized. It can be coated on a copper foil substrate to be used as a current collector for a dendrite‐free Li metal anode. OBHcCs effectively reduces the local current density owing to the high surface area and inhibits Li dendrite growth, which is explored by scanning electron microscopy and an X‐ray photoelectron spectra depth profile. The abundant lithiophilic oxygen and boron‐containing functional groups reduce the potential barrier of nucleation and lead to the homogeneous Li ions flux as confirmed by the density functional theories. Therefore, the Li metal anode based on OBHcCs (OBHcCs@Li) stably runs for 700 h in a symmetric cell with a Li stripping capacity of 1 mAh cm −2 at 1 mA cm −2 . Furthermore, the OBHcCs@Li|LiFePO4 full cell shows a good capacity retention of 84.6% with a high coulombic efficiency of 99.6% at 0.5 C for 500 cycles. Abstract : An oxygen and boron codoped honeycomb carbon skeleton allows lithium to grow along the skeleton, guiding heterogeneous nucleation and uniform deposition of lithium. In addition, it maintains the structural integrity after lithium exfoliation. The abundant lithiophilic oxygen and boron‐containing functional groups, such as BCO2 and BC2 O bonds, enhance the adsorption of lithium (Li)‐ion for uniform Li‐ion transport flux.